Breaking glass ceilings in Colombia: Strategies and outcomes in efforts to narrow the gender gap in educational leadership - Gregory Elacqua; Graciela Perez Nunez; Pedro Cubillos; Juliana Iglesias (Inter-American Development Bank (IDB), 2025)
In Colombia, women represent 65% of the teacher workforce but only 34% of school principals, reflecting a significant gender gap in leadership. This study examines two centralized principal selection processes implemented by Colombias National Civil Service Commission: the 2016 nationwide process and the 2018 process targeting disadvantaged PDET regions (Development Programs with a Territorial Focus). Both processes evaluated candidates through standardized tests, minimum requirements, and assessments of education and experience, determining eligibility for leadership vacancies. Our descriptive analysis shows how selection criteria influence gender representation. In 2016, standardized testing dominated, resulting in 45% of applicants being women but only 20% qualifying, with an overall eligible-to-vacancy ratio of just 0.7%. In contrast, the 2018 PDET process prioritized context-specific competencies and practical experience, yielding 35% female eligibility despite women comprising only 38% of applicants (likely due to challenging conditions in PDET regions). Moreover, eligible candidates of both genders outnumbered vacancies by 4.5 times. These findings underscore the critical role of selection design in shaping gender representation in school leadership. However, structural barriers, such as inadequate childcare and rigid work schedules, persist as obstacles to womens participation.
Keywords: I21; I24; J71; J16; M51; O15; 330; gender gap; educational leadership; school management; recruitment process; diversity in leadership; Latin America; Colombia